New Strangers in Paradise : The Immigrant Experience and Contemporary American Fiction - Muller, Gilbert H., 1941- (Book collections on Project MUSE., 1999)
New Strangers in Paradise offers the first in-depth account of the ways in which contemporary American fiction has been shaped by the successive generations of immigrants to reach U.S. shores. Gilbert Muller reveals how the intersections of peoples, regions, and competing cultural histories have remade the American cultural landscape in the aftermath of World War II. Muller focuses on the literature of Holocaust survivors, Chicanos, Latinos, African Caribbeans, and Asian Americans. In the quest for a new identity, each of these groups seeks the American dream and rewrites the story of what it.